Binary Plane Technique Based Color Quantization for Content Based Image Retrieval - Esther Ratna, T; Subash Chandra, N (International Journal of Engineering and Technology, 2018)
Extracting accurate informative file from a high volume of graphic files is a challenging task. This paper focus on presenting a new color indexing approachÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â using the histogram features. Two histogram features like maximum color histogram and minimum color histogram are computed and are vector quantized to constitute a feature vector. Bit plane technique is used to map these features based upon it value at the respective position. The ultimate goal of any retrieval method is to attain higher precision within a short span of time that could be achieved if the data is in compressed to accomplish this the image is compressed using binary plane technique. The result analysis depicts the performance of the proposed approach under lossy and lossless modes and found that when operated in lossy it attain effective precision rate in a speculated amount of time.Â